Performance of growing pigs of different genetic groups fed varying dietary protein levels - F.O.I. Anugwa; A.I. Okwori (African Journal of Pig Farming, 2016)
Two feeding experiments were conducted, using a 2 x 2 factorial design, to determine the performance of two genetic groups of pigs fed two protein levels in each case. Each experiment was replicated three times. In the first experiment, 24 pigs, 12 each of indigenous Nigerian pigs (LC) and Large White x Indigenous cross-breeds (LW x LC) with average initial weights of 7.3 and 10.2 kg, respectively, were fed isocaloric (3.1 Mcal of ME/Kg) diets containing 12 or 16% crude protein for seven weeks. In the second experiment, 12 Large White (LW) pigs and 12 LW x LC pigs with average initial weights of 12.5 and 11.8 Kg, respectively, were fed isocaloric (3.1 Mcal of ME/Kg) diets containing 14 or 18% crude protein for seven weeks. Overall, the LC pigs performed better than the LW x LC pigs on the lower (12%) protein diet while the LW x LC pigs performed better than the LC pigs on the 16% protein diet. In experiment 2, the LW x LC pigs performed better than the LW pigs on the lower (14%) protein diet while the LW pigs performed better than the LW x LC pigs on the 18% protein diet.